Pengaruh Leverage, Sales Growth, Dan Corporate Social Responsibility, Terhadap Tax Aggressiveness - I Dewa Gede Sathya Gunawan; I Putu Deddy Samtika Putra; I Wayan Budi Satriya (Hita Akuntansi dan Keuangan, 2026)
Tax revenue constitutes the primary source of income for the Indonesian government; however, the tax-to-GDP ratio remains relatively low compared to other countries in the Asia-Pacific  region. This low ratio reflects suboptimal tax collection, which is partly attributed to corporate tax aggressiveness. Tax aggressiveness refers to strategies employed by companies to minimize their tax liabilities through both legal and illegal tax planning mechanisms. This study aims to examine the influence of leverage, sales growth, and corporate social responsibility (CSR) on tax aggressiveness among energy sector companies listed on the Indonesia Stock Exchange during the 2021–2023 period. A quantitative research method was employed, utilizing a purposive sampling approach. Data analysis was conducted using multiple linear regression. The findings indicate that both leverage and sales growth exert a positive and significant effect on tax aggressiveness, whereas corporate social responsibility has a negative and significant impact. These results suggest the need for stricter oversight of corporate financing structures and sales growth within the energy sector, as these factors may contribute to aggressive tax practices. Accordingly, the government and tax authorities are encouraged to formulate policies that promote fiscal transparency.